Conscious and unconscious processing of facial expressions: Evidence from two split‐brain patients. Issue 1 (11th December 2013) - Prete, Giulia; D'Ascenzo, Stefania; Laeng, Bruno; Fabri, Mara; Foschi, Nicoletta; Tommasi, Luca
<x xml:space="preserve">Abstract</x> We investigated how the brain's hemispheres process explicit and implicit facial expressions in two 'split‐brain' patients (one with a complete and one with a partial anterior resection). Photographs of faces expressing positive, negative or neutral emotions were shown either centrally or bilaterally. The task consisted in judging the friendliness of each person in the photographs. Half of the photograph stimuli were 'hybrid faces', that is an amalgamation of filtered images which contained emotional information only in the low range of spatial frequency, blended to a neutral expression of the same individual in the rest of the spatial frequencies. The other half of the images contained unfiltered faces. With the hybrid faces the patients and a matched control group were more influenced in their social judgements by the emotional expression of the face shown in the left visual field (LVF). When the expressions were shown explicitly, that is without filtering, the control group and the partially callosotomized patient based their judgement on the face shown in the LVF, whereas the complete split‐brain patient based his ratings mainly on the face presented in the right visual field. We conclude that the processing of implicit emotions does not require the integrity of callosal fibres and can take place within subcortical routes lateralized in the right hemisphere.